E-learning for postgraduate students - Kavitha D/O Ginanam. (2011)
E-learning has become very popular and is an ideal platform for higher learning education. It has been extensively used in universities, polytechnics and colleges to meet the challenges and the rising demands of modern education. It facilitates in permitting more people to access the course materials in a very convenient manner.